POLICY IN THE ERA OF PANDEMIC: IS GOVERNMENT’S LEGAL CULTURE AFFECTING? - Anggraeni, Ricca; Sari, Indah Mutiara (Jurnal Dinamika Hukum, 2021)
During the era of pandemic, the government was required to formulate policies that could protect its citizens from the spread of the pandemic, and also all the effects that were present because of it. Unfortunately the Government is too late to take steps to anticipate the spread of Covid-19 Pandemic in Indonesia. And as the consequence, various policies are implemented, ranging from general policies to policies in the implementation technical level. As a result, several policies have been ignored by the community, ranging from the provisions of the Large-Scale Social Restrictions regulated through Government Regulations, to the technical provisions concerning restrictions on the travel of people in the context of acceleration of handling Covid-19. Social reality shows that the policies taken by the Government have not been successfully obeyed by the Indonesian people. Through Foucault's theory of power relations, it can be stated that the Government has lost its power during the Covid-19 Pandemic, because regulation as a reflection of the Government's power has not been demanded by the public. An interesting problem is, it turns out that the legal culture that lives in the community is not the cause of these neglection, but the legal culture of the Government itself in determining various policies during the pandemic is the main cause.Keywords: Covid-19 Pandemic; Legal Culture; Policy